A chitosan gold nanoparticles molecularly imprinted polymer based ciprofloxacin sensor - Surya, Sandeep G; Khatoon, Shahjadi; Ait Lahcen, Abdellatif; Nguyen, An T. H; Dzantiev, Boris B; Tarannum, Nazia; Salama, Khaled N (RSC advances, 2020)
In this work, we present a novel study on the development of an electrochemical biomimetic sensor to detect the ciprofloxacin (CIP) antibiotic. A chitosan gold nanoparticles decorated molecularly imprinted polymer (Ch-AuMIP) was used to modify the glassy carbon electrode (GCE) for preparation of the sensor. The Ch-AuMIP was characterized to understand various properties like chemical composition, morphology, roughness, and conduction using Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), atomic force microscopy (AFM) and cyclic voltammetry (CV) respectively. Several experimental conditions affecting the Ch-AuMIP/GCE sensor such as the CIP removal agent, the extraction time, the volume of Ch-AuMIP drop-cast onto GCE and the rebinding time were studied and optimized. The Ch-AuMIP sensor sensitivity was studied in the concentration range of 1-100 μmol L −1 exhibiting a limit of detection of 210 nmol L −1 . The synergistic combination of Au nanoparticles and Ch-MIP helps detect the CIP antibiotic with good sensitivity and selectivity, respectively. We investigated the selectivity aspect by using some possible interfering species and the developed sensing system showed good selectivity for CIP with a 66% response compared to the other compounds (≤45% response). The proposed sensing strategy showed its applicability for successful detection of CIP in real samples like tap water, mineral water, milk, and pharmaceutical formulation. The developed sensor showed good selectivity towards CIP even among the analogue molecules of Norfloxacin (NFX) and Ofloxacin (OFX). The developed sensor was successfully applied to determine the CIP in different samples with a satisfactory recovery in the range of 94 to 106%. In this work, we present a novel study on the development of an electrochemical biomimetic sensor to detect the ciprofloxacin (CIP) antibiotic.